Reliability analysis of passive residual heat removal system for large advanced pressurized water reactors - Li, Tianrui; Xiao, Xinkun; Lu, Guoqing; Chen, Shikang; Chen, Ronghua; Tian, Wenxi (Frontiers in Nuclear Engineering, 2025)
This paper focuses on the passive residual heat removal system of a typical large advanced pressurized water reactor, analyzing its design, performance, and reliability during station blackout conditions combined with the failure of the auxiliary feedwater steam-driven pumps. The study employs modeling of passive safety systems and utilizes response surface methodology to evaluate system behavior during severe accident scenarios. Such comprehensive analysis contributes to ensuring the safe operation and advancement of nuclear power plants. The best-estimate program VITARS is used to analyze and calculate accident scenarios, with sensitivity analysis conducted based on preliminary thermal-hydraulic calculations to optimize parameter selection and simplify the response surface model structure, thereby streamlining the analysis process. An artificial neural network is employed as a surrogate model for complex thermal-hydraulic calculations, significantly improving analysis efficiency. The findings indicate that the passive residual heat removal system has zero failure probability under normal uncertainty ranges within 72 h. Even under extreme conditions, such as delayed opening of the steam generator’s safety valve, the system maintains reactor safety with a failure probability of only 0.035%.